Mathematical morphology and its applications to image and signal processing 10th International Symposium, ISMM 2011, Verbania-Intra, Italy, July 6-8, 2011. Proceedings - Soille, Pierre; Pesaresi, Martino; Ouzounis, Georgios K. (Berlin Heidelberg Springer, 2011)
This book contains the refereed proceedings of the 10th International Symposium on Mathematical Morphology, ISMM 2011 held in Verbania-Intra, Italy in July 2011. It is a collection of 39 revised full papers, from which 27 were selected for oral and 12 for poster presentation, from a total of 49 submissions.  Moreover, the book features two invited contributions in the fields of remote sensing, image analysis and scientific visualization. The papers are organized in thematic sections on theory, lattices and order, connectivity, image analysis, processing and segmentation, adaptive morphology, algorithms, remote sensing, visualization, and applications.
Electronic reproduction.
Keywords: Image processing -- Mathematics -- Congresses; Signal processing -- Mathematics -- Congresses; Digital filters (Mathematics) -- Congresses